Highly Uniform White Light-Based Visible Light Communication Using Red, Green, and Blue Laser Diodes - Jie Yang; Zhe Liu; Bin Xue; Zhou Liao; Liangsen Feng; Ning Zhang; Junxi Wang; Jinmin Li (IEEE Photonics Journal)
With the development of wireless optical communication and solid-state lighting, the high efficiency, large bandwidth, and high uniform white light source becomes more and more important. In this paper, a white light source generated by red, green, and blue laser diodes (RGB LDs) was synthetized according to the calculated power ratio of RGB LDs based on the chromaticity theory. The high coherence of the lasers normally leads to the nonuniform white light. Thus, it is to improve the illumination quality of the lighting source by employing micro lens for the purpose of homogenization. The simulation results showed that the uniformity of the white light incoherent radiation was above 90% which proves that the coherence of the lasers was destroyed. In addition, the photoelectric parameters of the RGB-LD mixed white light after homogenization was characterized. Meanwhile, the modulation bandwidth of RGB LDs before and after homogenization was analyzed, respectively, and it shows that the bandwidth was more than 1 GHz, which is limited by the photodetector cut-off frequency. Such a high-uniformity and high-speed RGB-LD mixed white light can be deployed for illumination and wireless communication simultaneously.